Penguatan Karakter Siswa Melalui Kearifan Lokal Budaya Tapanuli Selatan di Madrasah Batang Angkola - Aryani Hasugian; Ali Padang Siregar; Elissa Evawani Tambunan; Kasmawati; Ahmad Rafii; Nurzeddah (Yayasan Perguruan Kampus, 2023)
Strengthening character is a common trait that exists in society. Al Azhar Bi'ibadillah Tahalak Islamic Boarding School in South Tapanuli which always instills positive character in schools. In this activity, students previously did not understand character building in South Tapanuli culture. Through this activity, 50 students took part in this activity. This activity is within the South Tapanuli Culture. The community service team explains about Dalihan Natolu in relation to character strengthening. The method used in this activity is preparation, namely observation, implementation, evaluation and follow-up. Through this activity, the student response was obtained that 90% said they agreed with the activity and it attracted students so that students became more aware that character in culture is very important, this is because we as members of society must show positive character based on South Tapauli culture. which in spoken culture is highly valued in society. In Dalihan Natolu, there is also the strengthening of character, there is cooperation that is carried out when there is work in the community.